2017
DOI: 10.1038/tp.2017.192
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cognitive-behavioral therapy for obsessive-compulsive disorder involve robust and extensive increases in brain network connectivity

Abstract: Cognitive-behavioral therapy (CBT) is effective for obsessive compulsive disorder (OCD); however, little is understood about its mechanisms related to brain network connectivity. We examined connectivity changes from resting-state functional magnetic resonance imaging data pre-to-post-CBT in 43 OCD participants, randomized to receive either 4 weeks of intensive CBT or 4 weeks waitlist followed by 4 weeks of CBT, and 24 healthy controls before and after 4 weeks of no treatment. Network-based-statistic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…[113] Predictors of improvement with medication included pretreatment activation of the left superior temporal cortex and right cerebellum on symptom provocation task. [89] Studies investigating fMRI changes post-CBT have found improved connectivity between the cerebellum and widespread areas in the caudate, putamen, frontopolar cortex, DLPFC, and VLPFC[115] and normalization of increased left DLPFC and right OFC connectivity. [116] Predictors of improvement following CBT included baseline decreased basolateral amygdala (BLA)-VMPFC functional connectivity.…”
Section: Functional Imagingmentioning
confidence: 99%
“…[113] Predictors of improvement with medication included pretreatment activation of the left superior temporal cortex and right cerebellum on symptom provocation task. [89] Studies investigating fMRI changes post-CBT have found improved connectivity between the cerebellum and widespread areas in the caudate, putamen, frontopolar cortex, DLPFC, and VLPFC[115] and normalization of increased left DLPFC and right OFC connectivity. [116] Predictors of improvement following CBT included baseline decreased basolateral amygdala (BLA)-VMPFC functional connectivity.…”
Section: Functional Imagingmentioning
confidence: 99%
“…The OCD patients in our present series also showed a focus of decreased rCBF in the frontal operculum compared to the controls. The frontal operculum correlates with resistance to compulsions in OCD patients [32]. A functional MRI study reported that OCD patients showed lower spontaneous brain activity in the Rolandic operculum compared to healthy controls [33].…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, research demonstrates that compulsions or irresistible urges to act (as observed in OCD) are linked to impaired attentional capacity (7). Furthermore, interventions (e.g., cognitive behavioral therapy) that increase neural connectivity in the dorsolateral and ventrolateral prefrontal cortices (networks crucial for inhibitory control) are associated with greater resistance to compulsion (26). Accordingly, if used appropriately and with patients with good imagery ability, imagery-related treatments may strengthen activity in networks mediating conscious cognitive control.…”
Section: Advances In the Science Of Motor Imagery (Mi)mentioning
confidence: 99%